Borneo coast creatures of the mangrove - Agland, Phil; National Geographical Video (Stamford, CT: National Geographical Video, 1986)
Close look at the animals and plants which inhabit the mangrove swamps of the northwest coast of Borneo, and how they work together to survive
Editor, David Dickie
Narration: Richard Kiley
Keywords: Mangrove ecology -- Borneo; Mangrove forest -- Borneo